(untitled) (Innovate Conferences, 2025)
This article explores various methods used in teaching English in higher education institutions. It highlights the evolution of instructional strategies from traditional grammar-translation approaches to modern communicative and digital methods. The paper analyzes the strengths and limitations of each method and emphasizes the importance of adapting teaching styles to meet the needs of diverse learners in contemporary academic environments.